Assessment of radioactivity of 226Ra, 232Th and 40K in soil and plants for estimation of transfer factors and effective dose around Mkuju River Project, Tanzania - Banzi, F; Msaki, P; Mohammed, N (National Mining University, 2017)
Purpose. To establish pre-mining indicators to assess radiological impact as a result of release of radionuclides to environment during uranium mining at Mkuju River Project radioactivity of 226Ra, 232Th and 40K in soil, plants, fruits and cereals. Methods. The High Purity Germanium detector was used to determine the radioactivity and the data were subsequently used to establish soil to plant transfer factors and annual effective dose. Findings. The results revealed a strong positive correlation (r) of 0.947 and 0.950 for 226Ra and 232Th, respectively, between values determined in soils and plants. Implicit in these finding is that the distribution of radionuclides in soils is directly proportional to the corresponding radionuclides in plants. Originality. The roots of wild grass had the highest specific radioactivity (Bqkg-1) for 226Ra (2.15 ± 0.02), 232Th (1.43 ± 0.02) and 40K (198.16 ± 1.72) and the roots of cabbage had the highest values for 226Ra (1.38 ± 0.04), 232Th (1.34 ± 0.03) and 40K (146.12 ± 1.02) among the food crops, an indication of a higher ability to uptake radionuclides from soil. Similarly, since the TFs were found higher in wild grass for 226Ra (0.0533 ± 0.04), 232Th (0.0374 ± 0.002) and 40K (0.5297 ± 0.05) and cabbage for 226Ra (0.0362 ± 0.03), 232Th (0.0360 ± 0.001) and 40K (0.4173 ± 0.05). Practical implications. It is an evident that these plants can serve as good bio indicators to assess release of radionuclides from inside the mining site to the public domain. Moreover, the annual effective dose (mSvy-1) for 40K (0.23 ± 0.02), 226Ra (0.046±0.004) and 232Th (0.073 ± 0.006) in edible crops when consumed in the vicinity of the MRP before the mining operations were, as expected, insignificant.

Мета. Встановити показники радіологічного впливу викиду радіонуклідів на навколишнє середовище під час видобутку урану на родовищі “Мкужу-Рівер”, а саме 226Ra, 232Th та 40K у ґрунті, рослинах, фруктах та злаках. Методика. Для визначення радіоактивності використовувався детектор високочистого германію. Отримані дані були використані для визначення факторів переносу й ефективної дози для ґрунту і рослин. Результати. Результати виявили сильну позитивну кореляцію (r) 0.947 і 0.950 226Ra та 232Th, відповідно, між отриманими значеннями в ґрунтах та рослинах. Розподіл радіонуклідів у ґрунтах прямо пропорційний відповідним радіонуклідам рослин. Наукова новизна. Найвища питома радіоактивність (Бк/кг-1) зафіксована в коріннях трави – 226Ra (2.15 ± 0.02), 232Th (1.43 ± 0.02) та 40K (198.16 ± 1.72), а корені капусти мають найвищі значення радіоактивності серед харчових культур – 226Ra (1.38 ± 0.04), 232Тh (1.34 ± 0.03) та 40 К (146.12 ± 1.02), що свідчить про більш високу здатність поглинати радіонукліди з ґрунту. Аналогічно, найвищий фактор переносу зафіксований у коріннях трави – 226Ra (0.0533 ± 0.04), 232Тh (0.0374 ± 0.002) та 40К (0.5297 ± 0.05) та капусти – 226Rа (0.0362 ± 0.03), 232Тh (0.0360 ± 0.001) та 40К (0.4173 ± 0.05). Практична значимість. Встановлено, що рослини можуть служити хорошими біоіндикаторами для загальнодоступної оцінки викиду радіонуклідів із гірничодобувної ділянки. Крім того, щорічна ефективна доза (мСв-1) для 40К (0.23 ± 0.02), 226Rа (0.046 ± 0.004) та 232Тh (0.073 ± 0.006) в їстівних культурах, що споживаються в околицях уранового родовища “Мкужу-Рівер” до початку його розробки, як і очікувалося, є незначною.

Цель. Установить показатели радиационного воздействия выброса радионуклидов в окружающую среду при добыче урана на месторождении “Мкужу Ривер”, а именно 226Ra, 232Th та 40K в почве, растениях, фруктах и злаках. Методика. Для определения радиоактивности использовался детектор высокочистого германия. Полученные данные были использованы для определения факторов переноса и эффективной дозы для почвы и растений. Результаты. Результаты выявили сильную положительную корреляцию (r) 0.947 и 0.950 226Ra и 232Th, соответственно, между полученными значениями в почвах и растениях. Распределение радионуклидов в почвах прямо пропорционально соответствующим радионуклидам растений. Научная новизна. Наивысшая удельная радиоактивность (Бк/кг-1) зафиксирована в корнях травы – 226Ra (2.15 ± 0.02), 232Th (1.43 ± 0.02) и 40K (198.16 ± 1.72), а корни капусты имеют наивысшие значения радиоактивности среди пищевых культур – 226Ra (1.38 ± 0.04), 232Тh (1.34 ± 0.03) и 40 К (146.12 ± 1.02), что свидетельствует о более высокой способности поглощать радионуклиды из почвы. Аналогично, наивысший фактор переноса зафиксирован в корнях травы – 226Ra (0.0533 ± 0.04), 232Тh (0.0374 ± 0.002) и 40К (0.5297 ± 0.05) и капусты – 226Rа (0.0362 ± 0.03), 232Тh (0.0360 ± 0.001) и 40К (0.4173 ± 0.05). Практическая значимость. Установлено, что растения могут служить хорошими биоиндикаторами для общедоступной оценки выброса радионуклидов с горнодобывающего участка. Кроме того, ежегодная эффективная доза (мСВ-1) для для 40К (0.23 ± 0.02), 226Rа (0.046 ± 0.004) и 232Тh (0.073 ± 0.006) в съедобных культурах, потребляемых в окрестностях уранового месторождения “Мкужу-Ривер” до начала его разработки, как и ожидалось, является незначительной.
Keywords: radioactivity; transfer factors; effective dose; Mkuju River; Tanzania